Respuesta :
Answer:
c.
[tex]\frac{5}{4} x - 2 = \frac{3}{2} x-4[/tex]
Step-by-step explanation:
a.
[tex]\frac{5}{2} x +\frac{7}{2} =\frac{3}{4} x+14 \\\frac{5}{2}x -\frac{3}{4} x=14-\frac{7}{2} \\\frac{10-3}{4} x =\frac{28-7}{2} \\\frac{7}{4} x =\frac{21}{2} \\x = \frac{21}{2} * \frac{4}{7} = 6 \\[/tex]
b.
[tex]\frac{5}{4} x -9 = \frac{3}{2} x-12 \\\frac{5}{4} x - \frac{3}{2} x= -12 + 9 \\\frac{5-6}{4} x = -3 \\\frac{-1}{4} x = -3 \\x = -3 * -4 \\x = 12[/tex]
c.
[tex]\frac{5}{4} x-2=\frac{3}{2} x-4 \\\frac{5}{4} x-\frac{3}{2} x=-4+2 \\\frac{5-6}{4}x=-2 \\\frac{-1}{4} x = -2 \\x = -2 * -4 \\x = 8[/tex]
d.
[tex]\frac{5}{2} x -7 = \frac{3}{4} x+14 \\\frac{5}{2}x -\frac{3}{4} x=14+7 \\\frac{10-3}{4} x =21 \\\frac{7}{4} x =21 \\x = 21 * \frac{4}{7} = 12 \\[/tex]
You could also replace x for 8 in every equation and see if both sides give the same answer